Causal effect of mergers and acquisitions on EU bank productivity - Abdussalam Aljadani; Hassen Toumi (Journal of Economic Structures, 2019)
This paper examines the causal effect of mergers and acquisitions (M&A) on bank productivity (Q) in 23 European Union countries and the short- and long-term relationship among fixed assets (k1), liquid assets (k2), and labour (L) over the period 1990-2013 for a sample of 156 commercial banks, of which 60 entities have acquired at least one other entity. Granger causality tests on our results reveal unidirectional causality from liquid assets to fixed assets. However, the causality between K2 and L is unobservable, and the linkage between fixed assets and labour is bidirectional. The error correction term (ECT) is negative and statistically significant for all models, which denotes the presence of bidirectional relationship among all selected variables and long-term unidirectional causality from mergers and acquisitions to bank productivity. Our long-term dynamic panel estimates indicate that the strategic fit of mergers and acquisitions has the potential to create long-term productivity improvement.
Keywords: L11; G15; G21; G24; 330; Mergers and acquisitions (M&A); Productivity; Panel cointegration techniques